2012
DOI: 10.1590/s1516-35982012001000010
|View full text |Cite
|
Sign up to set email alerts
|

Digestible tryptophan:lysine ratio for laying hens

Abstract: -The objective of this study was to evaluate the requirement of digestible tryptophan for white laying hens in the production stage fed diets of different digestible tryptophan:digestible lysine ratios, as well as animal performance and histological alterations in their reproductive and digestive systems. A total of 280 white laying hens at 29 weeks of age were distributed in a completely randomized design with five treatments and seven replications with eight birds in each. The treatments consisted of a base … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 11 publications
(10 reference statements)
7
8
0
Order By: Relevance
“…The ideal digestible tryptophan:digestible lysine ratio of 0.252, estimated in this study based on the efficiency of utilization of digestible lysine for production of eggs mass was similar to the ratio of 0.253 estimated by Lima et al (2011), based on the feed conversion per dozen eggs of hens from 29 to 45 weeks of age.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The ideal digestible tryptophan:digestible lysine ratio of 0.252, estimated in this study based on the efficiency of utilization of digestible lysine for production of eggs mass was similar to the ratio of 0.253 estimated by Lima et al (2011), based on the feed conversion per dozen eggs of hens from 29 to 45 weeks of age.…”
Section: Resultssupporting
confidence: 80%
“…The feed conversion per dozen eggs was not affected (P>0.05) by dietary digestible tryptophan levels in diets. The digestible tryptophan: digestible lysine ratio of 0.252 estimated in this study was higher than the value found by Lima et al (2011) for feed conversion per eggs mass (0.246%); however, it was similar to the value obtained by the same authors for feed conversion per dozen eggs (0.253%) of hens from 29 to 45 weeks of age.…”
Section: Resultssupporting
confidence: 68%
“…However, Russell & Harms (1999) observed that only levels of tryptophan lower than or equal to 0.130% promoted reduction in the egg mass produced by laying hens of 55 to 59 weeks of age. The ideal ratio of 24.3% estimated for feed conversion per egg mass, found in the present study, was similar to the 24.6% obtained by Lima et al (2012) As occurred in this present study, in experiments aimed to establish ideal ratios between essential amino acids and lysine, it is ideal that the feed intake of the birds for different treatments not present significant variation. A variation in feed intake results in variation in the amount of digestible lysine consumed, which could influence the performance parameters and mask the estimated ideal ratio.…”
supporting
confidence: 90%
“…Taking the feed conversion per egg mass into account, the estimated ideal digestible tryptophan-to-digestible lysine ratio was 24.3%. This value was similar to the 24.6% estimated by Lima et al (2012) based on the feed conversion per egg mass of hens of 29 to 45 weeks of age. This ratio was higher than the values obtained by Deponti et al (2007), who concluded that depending on the trait (production or egg mass) and on the regression model applied on data analyses (quadratic, exponential or segmented), the ideal tryptophan-tolysine ratios for laying hens of 53 to 58 weeks of age are in the range of 17.4 to 20.3%.…”
supporting
confidence: 88%
See 1 more Smart Citation